You shall not enter the list: Inscriptional Practices and Politics of Deservingness in Indonesia - Hestu Prahara (Antropologi Indonesia, 2018)
Indonesia first state-led community-driven development (CDD) began in the 1990s with influential support by the World Bank. This paradigm sees community not merely as an object but rather as an active subject of development. To ensure the shifting in the paradigmatic level, a social engineering process known as community empowerment project was built using monitoring instrument to guarantee inclusive development planning, prevent elite capture, and promote internal audit capacities. In this process, extensive use of bureaucratic instruments, e.g., paperwork, assessment forms, official stamps, program proposals/reports, and financial report facilitate the formation of community participation. How the use of documents shaped the intended inclusive development projects under CDD paradigm? This paper discusses the ironic trends of how participatory framework in CDD, in fact, intensified social exclusions. The discussion is based on my experience observing the implementation of ‘public consultation approach’ in PBDT 2015 (Pemutakhiran Basis Data Terpadu/ Unified Database Updating). In such program, the local stakeholders, together with community trustee at kelurahan (village) level held a meeting to verify the enlisted poor households. The verification was crucial to create a unified database that can be used for future reference of the beneficiaries for several social assistance programs in Indonesia. I argue that tensions and negotiations toward deciding which names deserve to be on the list perpetuated forms of exclusion that embrace the exercise of prejudice, ethnic, and moral references in producing the hierarchy of deservingness at the community level.